2011
DOI: 10.4103/0974-2700.82206
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis and outcome predictors of traumatic head injury in childhood: Analysis of 454 observations

Abstract: Aim:To determine factors associated with poor outcome in children suffering traumatic head injury (HI).Materials and Methods:A retrospective study over an 8-year period including 454 children with traumatic HI admitted in the Intensive Care Unit of a university hospital (Sfax-Tunisia). Basic demographic, clinical, biological and radiological data were recorded on admission and during the ICU stay. Prognosis was defined according Glasgow outcome scale (GOS) performed after hospital discharge by ICU and pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
(78 reference statements)
13
20
0
1
Order By: Relevance
“…Pediatric patients and the elderly are more likely to die. [24] and this is also the finding in this series.…”
Section: Discussionsupporting
confidence: 88%
“…Pediatric patients and the elderly are more likely to die. [24] and this is also the finding in this series.…”
Section: Discussionsupporting
confidence: 88%
“…After controlling for exogenous administration of mannitol and hypertonic saline, the association between hypernatremia and mortality persisted (18, 19). These studies did not specifically look at the change in sodium over time.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of three patients reported EVD associated severe dehydration (22). In a series of children who suffered traumatic brain injury, severe hyponatremia < 125 meq/dL was associated with increased mortality (18). Williams et al evaluated 2,343 patients who underwent brain tumor resection and found hyponatremia occurred in 8.7% of patients (3).…”
Section: Discussionmentioning
confidence: 99%
“…An example of the pediatric risk prediction scores, the Pediatric Risk of Mortality (PRISM III) [5], is a widely used scoring mechanism in pediatric ICU (PICU) [9] that has been validated in various settings as both an individual predictor and a significant predictor in a multivariate model in the United States and internationally [13][14][15][16][17][18][19][20][21]. A state-of-the-art scheme, PRISM III has an additive stepwise structure that relies on 17 physiological variables and 26 ranges.…”
Section: Pediatric Population Risk Scoresmentioning
confidence: 99%